Analytical study on high-speed railway track deformation under long-term bridge deformations and interlayer degradation. (February 2021) - Gou, Hongye; Xie, Rui; Liu, Chang; Bao, Yi; Pu, Qianhui
Highlights: The paper studies high-speed railway track deformation that affects safety of trains. Long-term bridge deformations and interlayer degradation are considered. Closed-form solutions are presented and compared with sophisticated finite element model. The investigated deformations include pier settlement, fault of beam, and beam end rotation. The effect of fastener stiffness on track deformation is investigated. Abstract: Bridges are subjected to long-term deformations in addition to deformations under design loads. In high-speed railway bridges, long-term bridge deformation and potential degradation of materials may adversely impact the operation safety and riding comfort of the railway. While a high-speed railway network is being established in China, it is significant to understand the effects of long-term bridge deformation on track deformation for effective asset management. This study aims to develop an analytical model to investigate the roles of long-term bridge deformations and bridge-track interlayer degradation. Mechanical analysis is conducted to develop a track-bridge deformation model and derive closed-form solutions that can be applied in design and evaluation of high-speed railway bridges. The analytical study is validated against a three-dimensional finite element model, and used to investigate the effects of key parameters (e.g. bridge deformation amplitude, span length, fastener stiffness, and mortar layer stiffness). This study provides a method to quantitatively evaluate track deformation due to bridge deformations and interlayer degradation. With the developed formulae, real-time condition assessment of high-speed railway track can be performed based on real-time monitoring of bridge deformations.